The Costume as a Mask of Identity - Soares Junior, Glauber (2025)
Understanding that costumes in cinematic works are used for the subjective and objective construction of characters, this article aims to analyze the meanings attributed to costume design in the symbolic shaping of the protagonists in the film Passing (2021). To achieve this, a semiotic reading—both denotative and connotative—was conducted on four costume images from the film, highlighting that the clothing in the selected scenes played a significant role in the narrative. The film is set in 1920s New York, a context marked by racial segregation, and its English title, Passing, symbolically addresses the issues of color- ism. The narrative follows Black characters who pass as white to access spaces from which they are otherwise excluded. Regarding the main findings, the costume design—comprising long dresses, stockings, gloves, and hats—functions as a mask that conceals true identities.